2011
DOI: 10.1055/s-0030-1256440
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine-needle aspiration of pancreatic cystic lesions provides inadequate material for cytology and laboratory analysis: initial results from a prospective study

Abstract: Although EUS-guided FNA was technically feasible in the majority of patients with pancreatic cystic lesions (87 %), it was possible to obtain a classifying cytopathologic diagnosis and a chemical analysis in only a third and a half of cases, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
96
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 19 publications
6
96
1
2
Order By: Relevance
“…Turk J Gastroenterol 2014; 25: 1-18 malignancy is around 25% (from 8% to 29-36%) (27,45,47,48). Cytological yield is poor with EUS-FNA: Cytology was positive in only 29% of malignant mucinous tumours.…”
Section: şEntürk H Management Of Cystic Diseases Of the Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…Turk J Gastroenterol 2014; 25: 1-18 malignancy is around 25% (from 8% to 29-36%) (27,45,47,48). Cytological yield is poor with EUS-FNA: Cytology was positive in only 29% of malignant mucinous tumours.…”
Section: şEntürk H Management Of Cystic Diseases Of the Pancreasmentioning
confidence: 99%
“…The cytologic yield of EUS-FNA is rather poor: The overall accuracy of EUS-FNA cytology was reported as 50% (24)(25)(26). Interim analysis of a recent study demonstrated that the rate of sufficient material is 49 % for fluid analysis and, 31% for cytology (27). However the yield may be increased with some special techniques as puncturing the wall at the expense of increased risk of pancreatitis (28).…”
Section: Eus: Diagnostic Performancementioning
confidence: 99%
“…Several recent studies demonstrate that even with the use of fine needle aspiration (FNA) during endoscopic ultrasound, the accuracy of the preoperative diagnostic work-up does not significantly increase [11] . The sensitivity of FNA cytology is around 38% [12] , while combined biochemistry and cytology provides a correct diagnosis in only 33% [13,14] . For this reason, there is a concrete danger of over-or underestimation of the risk of malignant transformation in some lesions and, as a consequence, of over-or undertreatment of the patients.…”
Section: Editorialmentioning
confidence: 99%
“…Although biochemical markers such as carcinogenic embryonic antigen (CEA) and amylase measured in cyst fluid aspirates are frequently used to aid in diagnosis of pancreatic cysts, the authors focused on cytologic yield from EUS-FNA. In the literature, the overall yield of EUS-FNA for cytologic analysis of indeterminate pancreatic cystic lesions is 31-37 % [2,4].Morphologic features noted by high resolution EUS images of small pancreatic cysts can help differentiate mucinous-type cysts from others. Nevertheless, in a recent study, expert endosonographers were evaluated for their ability to make a diagnosis of pancreatic MCN based on EUS appearance alone without FNA.…”
mentioning
confidence: 99%
“…Although biochemical markers such as carcinogenic embryonic antigen (CEA) and amylase measured in cyst fluid aspirates are frequently used to aid in diagnosis of pancreatic cysts, the authors focused on cytologic yield from EUS-FNA. In the literature, the overall yield of EUS-FNA for cytologic analysis of indeterminate pancreatic cystic lesions is 31-37 % [2,4].…”
mentioning
confidence: 99%